Engineering psychology and cognitive ergonomics : 15th International Conference, EPCE 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, proceedings /: 15th International Conference, EPCE 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, proceedings. (2018) - Unknown
No abstract available